CEO NARCISSISM, CORPORATE GOVERNANCE, DAN KARAKTERISTIK PERUSAHAAN SEBAGAI DETERMINAN PENGHINDARAN PAJAK - Jennifer Thurana; Indra Arifin Djashan (E-Jurnal Akuntansi TSM, 2026)
The purpose of this research is to obtain empirical evidence about the effect of CEO narcissism, board of size, female directors, company size, return on assets, leverage, and institutional ownership on tax avoidance. The population of this research consist of manufacturing companies listed in Indonesia Stock Exchange with a research period of 2022-2024. The sampling method used was purposive sampling, resulting in a sample of 130 companies and 390 data. The data was processed and analyzed using multiple regression with Statistical Program for Social Science (SPSS) software. The results of this research indicate that CEO narcissism, board of size, company size, return on assets and leverage have an effect on tax avoidance. However, female directors and institutional ownership have no effect on tax avoidance.